Draft Ninth Five Year Plan 1997-2002 and Annual Plan 1997-98 [Vol. II Statistical Statements] Union Territory of Chandigarh - Planning Commission (Planning Commission, 1997)
Major/Minor Headwise proposed Outlays for 9th Plan and Annual Plan 1997-98 Major Headwise detail of Continuing and New Schemes Physical Targets and Achievements Centrally Sponsored Schemes Basic Minimum Services (BMS)—Outlay and Expenditure Financial Outlay and Expenditure for Voluntary Sector Women Component (WC) in the State Plan Programme-I: Financial Outlay.
Finance Department, Planning and Evaluation Organisation, Chandigarh Administration